High prevalence of sleep disordered breathing in patients with diabetic macular edema - Mason, R; West, S; Kiire, C; Groves, D; Lipinski, H; Jaycock, A; Chong, V; Stradling, JR (2012)
BACKGROUND: Diabetic retinopathy is more common and severe in patients with sleep disordered breathing (SDB). This study aimed to establish whether this is also true for patients with diabetic clinically significant macular edema (CSME). It is hypothesized that SDB, through intermittent hypoxia and blood pressure oscillations, might provoke worsening of CSME. METHODS: Patients with CSME had a home sleep study (ApneaLink; ResMed) to identify SDB. These results were compared with relevant control populations. Macular thickness was measured using optical coherence tomography, and retinal photographs were graded to assess the severity of retinopathy. RESULTS: Eighty of 195 patients (40 men) consented, with average age of 64.7 (11.7) years, neck circumference of 40.4 (5.4) cm, body mass index of 30.2 (6.2) kg/m, glycosylated hemoglobin (HbA1c) 7.8% (1.4%) [62 (8.0) mmol/mol], and Epworth sleepiness scale of 7.4 (4.8). Overall, 54% had an oxygen desaturation index ≥10, and 31% had an apnea-hypopnea index ≥15. This SDB prevalence is probably higher than would be expected from the available matched control data. Those with SDB were not sleepier, but they were older and more obese. No significant relationship was identified between the degree of macular thickness and the severity of SDB. CONCLUSION: Individuals with CSME have a high prevalence of SDB. Sleep disordered breathing may contribute to the pathophysiology of CSME, but the mechanism remains unclear. Given the high prevalence, retinal specialists should perhaps consider a diagnosis of SDB in patients with CSME. © Lippincott Williams and Wilkins.